PENGARUH MODAL USAHA DAN PENJUALAN TERHADAP LABA USAHA PADA PERUSAHAAN PENGGILINGAN PADI - Aslichah Aslichah; Sayekti S Dwiningwarni; Yulianto Yulianto; Supriyadi Supriyadi (J-MACC, 2018)
The motivator of this research is (Rahim and Dwi, 2016), and (Ma, Yiu and Nan Zhou, 2014). The agricultural sector is one of the important sectors that must be considered in providing food for the community. Research aims 1) to analyze the effect of business capital and sales on operating income partially, 2) to analyze the effect of business capital and sales on operating income simultaneously, 3) to analyze variables that have a dominant influence on operating income. The analysis method used is multiple linear regression method. Hypothesis 1) it is suspected that there is a positive and significant influence between business capital and sales on operating income partially, 2) it is suspected that there is a positive and significant influence between business capital and sales on operating income simultaneously, 3) alleged sales variables have a dominant influence on operating income. The results of the study: 1) there is a positive and significant influence between business capital on operating income, 2) there is a positive and significant influence between sales and operating income, 3) there is a positive and significant influence between business capital and sales on operating income simultaneously , 4) variable business capital has a dominant effect on operating income.